An assessment of the implementation of the HIV workplace policy in Akwa Ibom State: a cross-sectional descriptive study - Idiong. H,M; Ekanem. A.M.; Udofia. E.A.; et al. (BMC Health Services Research, 2025)
Background Eliminating AIDS by 2030 will remain a mirage if obstacles to achieving zero new HIV infections and viral suppression, like stigma and discrimination against people living with HIV (PLHIV) are not eliminated. Several strategies and policies are targeted at this issue but it remains a huge challenge globally. Like other countries, Nigeria adopted the HIV in the Workplace policy (HIV WPP) in 2013, aimed at protecting the rights of PLHIV in the workplace. Akwa Ibom State (AKS), Nigeria, adopted this policy in 2014. However, since its adoption, its implementation has not been assessed. This study aimed to evaluate the availability and implementation of the HIV WPP in the state. Methods A cross-sectional study using a mixed methods research approach was conducted for 591 consecutively recruited employees and 43 employers/ decision-makers across 23 organizations. Data was collected from October 2022 to February 2023. Seven criteria based on the Policy Implementation Assessment Tool were used to assess policy implementation. Scores above 70% were categorized as optimal policy implementation. The chi-square test was used to determine the factors associated with the level of implementation of the policy. Results were analyzed using STATA 15.1 for quantitative and NVivo 10 for qualitative data. Results A total of 591 employees provided completed responses, the majority were females (59.7%) and 60.2% worked in government establishments. Of the employers, 55.6% were <45 years old, 59.1% were males, 72.7% had a university education and the median duration working as a manager was 5.5 years. Of the 22 assessed establishments, the policy was available in 1 (4.5%) organization and 95% had a suboptimal implementation of the policy. The unavailability of the policy and resources for implementation were deterrents to the level of implementation of the policy. Conclusion The level of implementation of the Akwa Ibom HIV in the workplace was suboptimal across both private and public sectors in the State. This was attributed to the unavailability of the policy and other resources for implementation. The State Agency for the Control of AIDS should consider improving access to the policy and strengthening implementation structures.
Research Article
Keywords: HIV; Stigma & discrimination; PLHIV